Idiopathic Hyperammonemia in a Patient with Total Pancreatectomy and Islet Cell Transplantation - Navaneethan, Udayakumar; Venkatesh, Preethi G K (JOP. Journal of the Pancreas, 2010)
Context Idiopathic hyperammonemia is characterized by elevated serum ammonia associated with neurological deterioration of no other obvious etiology associated with relatively normal liver function tests and normal amino-acid levels. Case report We report a case of a 32-year-old woman who presented with acute mental status changes with a pelvic abscess approximately a year following her total pancreatectomy and islet cell transplant surgery. Her ammonia level was elevated to 425 μg/dL. Traditional ammonia-reducing therapies were initiated, but proved ineffective. Metabolic, pharmacologic, microbial, and autoimmune causes for hyperammonemia were excluded. The patient ultimately required continuous veno-venous hemofiltration to decrease her ammonia. Ammonia levels decreased following continuous veno-venous hemofiltration and the patient’s mental status gradually returned to baseline. Conclusion Idiopathic hyperammonemia in the setting of total pancreatectomy and islet cell transplantation has not been reported before. We propose that malnutrition following total pancreatectomy resulting in repressed urea cycle enzyme synthesis may have predisposed for this hyperammonemia. Image: Liver biopsy showing signs of cholestasis with pericentral and pericellular fibrosis.